2020
DOI: 10.1038/s41419-020-2290-x
|View full text |Cite
|
Sign up to set email alerts
|

Locus-specific DNA methylation of Mecp2 promoter leads to autism-like phenotypes in mice

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disease with a strong heritability, but recent evidence suggests that epigenetic dysregulation may also contribute to the pathogenesis of ASD. Especially, increased methylation at the MECP2 promoter and decreased MECP2 expression were observed in the brains of ASD patients. However, the causative relationship of MECP2 promoter methylation and ASD has not been established. In this study, we achieved locus-specific methylation at the transcription start site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…We found both male and female offspring under early-life exposure had marked higher levels of methylation at the MeCP2 promoter and the less content of MeCP2 when compared with those under exposure during full gestation, which implied postnatal time was a sensitive window for perturbations of methylation. The same result was also observed in the frontal cortex of ASD patients and in the mice that was modified on at the ~ 500-bp TSS region of MeCP2 with a range of behavioral alterations, such as reduced social interaction [ 21 , 36 ]. In the prenatal period, MeCP2 acts on ADAM10/NOTCH signaling via miR-197 to disrupt the differentiation of neural progenitor cells into neurons [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
“…We found both male and female offspring under early-life exposure had marked higher levels of methylation at the MeCP2 promoter and the less content of MeCP2 when compared with those under exposure during full gestation, which implied postnatal time was a sensitive window for perturbations of methylation. The same result was also observed in the frontal cortex of ASD patients and in the mice that was modified on at the ~ 500-bp TSS region of MeCP2 with a range of behavioral alterations, such as reduced social interaction [ 21 , 36 ]. In the prenatal period, MeCP2 acts on ADAM10/NOTCH signaling via miR-197 to disrupt the differentiation of neural progenitor cells into neurons [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
“…We first analyzed the effect of Mecp2 gene deficiency on rat social behaviors at 8, 12, and 23 w. The frequency and duration of contact behaviors gradually increased with age among female Mecp2 +/+ rats but gradually declined with age among female Mecp2 +/− rats, and both parameters were significantly lower compared to female Mecp2 +/+ rats by 23 w ( Fig 2A and 2B ). We next analyzed self-grooming behavior during the social interaction test as higher frequency and longer duration are considered endophenotypic hyper-repetitive behaviors of autism spectrum disorder [ 21 23 ] and male Mecp2 mutant mice [ 24 26 ]. The frequencies ( Fig 3A ) of self-grooming were significantly reduced and the duration ( Fig 3B ) tended to be reduced but not significant in female Mecp2 +/− rats.…”
Section: Resultsmentioning
confidence: 99%
“…Various ASD-associated genes and receptors have been identified as the target of epigenetic alterations, such as SHANK3, MECP2, FMR1, etc. (Edamura and Pearson, 2005;Zhu et al, 2014;Yuksel et al, 2016;Lu et al, 2020). A histone acetylomewide association study published in 2016 carried out ChIPsequencing on 257 postmortem samples from individuals with ASD along with matched controls indicated that approximately 68% of ASD cases contained a mutual acetylome signature.…”
Section: Epigenomicsmentioning
confidence: 99%